Cytoplasmic-delivery of polyinosine-polycytidylic acid inhibits pancreatic cancer progression increasing survival by activating Stat1-CCL2-mediated immunity - Dongyu Zhang; Amit Kumar; Praveen Bhoopathi; Anjan K Pradhan; Santanu Maji; Padmanabhan Mannangatti; Jolene J Windle; Mark A Subler; Vignesh Vudatha; Jose G Trevino; Esha Madan; Azeddine Atfi; et al. (Journal for ImmunoTherapy of Cancer, 2023)
Background Pancreatic ductal adenocarcinoma (PDAC) is an aggressive cancer without effective therapies and with poor prognosis, causing 7% of all cancer-related fatalities in the USA. Considering the lack of effective therapies for this aggressive cancer, there is an urgent need to define newer and more effective therapeutic strategies. Polyinosine–polycytidylic acid (pIC) is a synthetic double-stranded RNA (dsRNA) which directly activates dendritic cells and natural killer cells inhibiting tumor growth. When pIC is delivered into the cytoplasm using polyethyleneimine (PEI), pIC-PEI, programmed-cell death is induced in PDAC. Transfection of [pIC]PEI into PDAC cells inhibits growth, promotes toxic autophagy and also induces apoptosis in vitro and in vivo in animal models.Methods The KPC transgenic mouse model that recapitulates PDAC development in patients was used to interrogate the role of an intact immune system in vivo in PDAC in response to [pIC]PEI. Antitumor efficacy and survival were monitored endpoints. Comprehensive analysis of the tumor microenvironment (TME) and immune cells, cytokines and chemokines in the spleen, and macrophage polarization were analyzed.Results Cytosolic delivery of [pIC]PEI induces apoptosis and provokes strong antitumor immunity in vivo in immune competent mice with PDAC. The mechanism underlying the immune stimulatory properties of [pIC]PEI involves Stat1 activation resulting in CCL2 and MMP13 stimulation thereby provoking macrophage polarization. [pIC]PEI induces apoptosis via the AKT-XIAP pathway, as well as macrophage differentiation and T-cell activation via the IFNγ-Stat1-CCL2 signaling pathways in PDAC. In transgenic tumor mouse models, [pIC]PEI promotes robust and profound antitumor activity implying that stimulating the immune system contributes to biological activity. The [pIC]PEI anti-PDAC effects are enhanced when used in combination with a standard of care (SOC) treatment, that is, gemcitabine.Conclusions In summary, [pIC]PEI treatment is non-toxic toward normal pancreatic cells while displaying strong cytotoxic and potent immune activating activities in PDAC, making it an attractive therapeutic when used alone or in conjunction with SOC therapeutic agents, potentially providing a safe and effective treatment protocol with translational potential for the effective therapy of PDAC.